Brand Fidelity Millennial Generation on Halal Cosmetic Brand Through Brand Experience and Brand Trust: The Role of Brand Love as Mediation - Murti Wijayanti; Dewi Sri Woelandari Pantjolo Giningroem; Novita Wahyu Setyawati (Majalah Ilmiah Bijak, 2023)
The study focuses on Millennials in Bekasi City to examine the relationship between brand experience, brand trust, brand love and brand loyalty. This study uses a quantitative approach with convenient sampling and survey methods to collect data from 100 respondents. In this study, data are analyzed using structural equation modeling (SEM) using Smart PLS software. Findings show that brand experience and brand trust have a positive impact on brand love. Furthermore, brand trust and brand love positively affect brand loyalty, whereas brand experience does not. The study also found that the relationship between brand experience and brand trust in terms of brand loyalty is mediated by brand love. This indicates that brand love plays a mediating role in the relationship between brand experience and brand trust in terms of brand loyalty. The research highlights the importance of emotional connection in building brand loyalty, especially for brands based on religion and beliefs. Marketers should focus on creating positive brand experiences, building consumer trust, fostering brand loyalty, and ultimately increasing brand loyalty.